Determination of Nitrogen Fixing Capacity of Bacteria Isolated from the Rhizosphere of Acacia Mangium from the BRIS Soil of Tembila, Besut, Terengganu, Malaysia - Nor Hasima, Mahmod; Abd Jamil, Zakaria; Nashriyah, Mat (2018)
The present study was conducted to isolate beneficial bacteria with nitrogen fixing potential from the rhizosphere of Acacia mangium plant. The plant grows wildly on the untouched area of problematic BRIS soil in Tembila, Terengganu. A total of 24 bacterial isolates were successfully sequestered from the soil samples using the Burk’s nitrogen free medium. Based on the preliminary morphology screening, eight bacterial isolates were selected and their morphological and biochemical characteristics were recorded. Three bacterial isolates namely UA1, UA6 and UAA2 were selected as final species for antibiotic sensitivity test and Acetylene Reduction Assay (ARA). All three bacterial isolates showed a high amount of nitrogenase activity in ARA with UA6 produced the highest and significant amount of ethylene with 18.55 nmolC2H4mL-1h-1. UA1 and UAA2 showed almost similar amount of ethylene with 17.10 and 17.00 nmolC2H4mL-1h-1 respectively. The isolated bacteria characteristics through all the test showed that these bacteria have potential to be explore for biofertilizer production industry.